The politics of identity : liberal political theory and the dilemmas of difference / Michael Kenny. - Kenny, Michael, 1951- (Polity, 2004)
A comprehensive and critical assessment of the ways in which Anglo-American political theorists have responded to the emergence of a politics of identity in democratic society.